1990
DOI: 10.1557/proc-189-215
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Controlled Processes in Microwave-Fired Oxide Ceramics

Abstract: Processing oxide-based ceramics using microwave ,leating leads to a number of unexpected results, which can only be interpreted in terms of enhanced diffusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(63 citation statements)
references
References 10 publications
0
62
1
Order By: Relevance
“…Until now, sintering behaviors of alumina have been most extensively investigated [18][19][20][21][22] and, in some cases, alumina/zirconia composites have also been investigated for the purpose of examining the effect due to the difference in absorptivity for millimeter-wave. 23) According to previous results, the decrease of densification temperature ranges from 100 to 400°C in millimeter-wave sintering of alumina.…”
Section: Millimeter-wave Sintering Of Alumina and Alu-mentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, sintering behaviors of alumina have been most extensively investigated [18][19][20][21][22] and, in some cases, alumina/zirconia composites have also been investigated for the purpose of examining the effect due to the difference in absorptivity for millimeter-wave. 23) According to previous results, the decrease of densification temperature ranges from 100 to 400°C in millimeter-wave sintering of alumina.…”
Section: Millimeter-wave Sintering Of Alumina and Alu-mentioning
confidence: 99%
“…According to the tracer experiment by Janney et al, 21) it was found that the activation energy of 18 O in sapphire is reduced to 60 % of its value in conventionally-heated sapphire. Enhancement in mass transfer has also indicated in the behavior of radial constriction of nano pore in alumina membrane under millimeter-wave radiation.…”
Section: Millimeter-wave Sintering Of Alumina and Alu-mentioning
confidence: 99%
“…[9][10][11] The difference in heating behavior between the two ovens is considered to be due to the difference in the electric field distributions in the oven. In the single-mode applicator, the electric field is more concentrated 12) in a certain area of the wave guide, which caused effective heating in the localized area and resulted in the thermal runaway, although its power was lower power than the multimode case.…”
Section: Single Mode Ovenmentioning
confidence: 99%
“…There are number of reports on the TRW by theoretical analysis 9) and by experimental work. 10) One of the causes for TRW is the heat spot 20) generated in a specimen, because of the permittivity difference in the existing phases or because of the selective heating. 21) Usually the permittivity of oxides increases as temperature, 22) so it is considered that the heating occurs selectively at high permittivity phases and the temperature increase is accelerated.…”
Section: Occurrence Of Thermal Runawaymentioning
confidence: 99%
“…1 Specific examples include microwave sintering of ceramics, [2][3][4][5] microwave-driven radioactive tracer ion diffusion, 6 microwave-driven ion-exchange reactions in glasses, 7 microwave joining of ceramics, 8 microwave ͑spin-odal͒ decomposition of solid solutions, 9 synthesis of metalcarbide powders, 10 and promotion of organic imidization reactions. 11 Understanding and explaining these observations has been complicated by difficulties in accurately characterizing the internal thermal state of a microwave-heated specimen.…”
Section: Introductionmentioning
confidence: 99%